Use of zygomatic implants for oral rehabilitation: literature review (Research, Society and Development, 2022)
The feasibility of rehabilitation of atrophic jaws comes from an evolution over the years, until entering the idealization and application of the installation of implants in the zygomatic bones. The literature shows a large percentage of success through the technique and acceptance among professionals in the area. Thus, for the complete success of the procedure performed, it is necessary to combine the knowledge of the anatomical structures, prior technical and practical knowledge, in addition to preoperative care, for planning, as well as trans and postoperative care, to complete the rehabilitation. The objective of the present work is to clarify the managements for rehabilitation in atrophic maxilla in order to increase the application of techniques such as the use of zygomatic implants in cases where the conventional technique is unfeasible. To develop the present work, researches carried out in PubMed, Scientific Electronic Library Online-SciELO and Google Scholar databases, based on articles in Portuguese, English and Spanish, aiming to support this literature review. Through a bibliographic survey, the authors concluded that the use of the technique of implants installed in the zygomatic bones for the rehabilitation of atrophic maxillae or with unfeasibility of the use of the conventional technique configures a more viable surgical procedure with a high percentage of success, when compared to rehabilitation. with conventional implants.